2022
DOI: 10.1101/2022.08.03.502652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methanol fixation is the method of choice for droplet-based single-cell transcriptomics of neural cells

Abstract: Single-cell transcriptomics methods have become very popular to study the cellular composition of organs and tissues and characterize the expression profiles of the individual cells that compose them. The main critical step in single-cell transcriptomics is sample preparation. Several methods have been developed to preserve cells after sample dissociation to uncouple sample handling from library preparation. Yet, the suitability of these methods depends on the types of cells to be processed. In this project, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Meanwhile, the use of cold-active proteases on kidney samples resulted in fewer artifacts, but inefficient tissue dissociation [26]. In addition, studies have shown that neural cell populations (NCPs) suspension without methanol preservation also experiences alterations in cellular composition and gene expression [27]. For fragile tissue biopsies, such as the pancreas or skin, which contain delicate cell populations, cryopreservation and cellular dissociation steps may introduce biases on the cellular composition.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the use of cold-active proteases on kidney samples resulted in fewer artifacts, but inefficient tissue dissociation [26]. In addition, studies have shown that neural cell populations (NCPs) suspension without methanol preservation also experiences alterations in cellular composition and gene expression [27]. For fragile tissue biopsies, such as the pancreas or skin, which contain delicate cell populations, cryopreservation and cellular dissociation steps may introduce biases on the cellular composition.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the use of cold-active proteases on kidney samples resulted in fewer artifacts, but inefficient tissue dissociation (22). In addition, studies have shown that neural cell populations (NCPs) suspension without methanol preservation also experiences alterations in cellular composition and gene expression (23). For fragile tissue biopsies, such as pancreas or skin, which contain delicate cell populations, cryopreservation and cellular dissociation steps may introduce biases on the cellular composition.…”
Section: Discussionmentioning
confidence: 99%
“…The Parse and 10x Fixed methods offered the advantage of cell fixation, allowing for potential sample storage and collection at multiple time points. This feature may be particularly beneficial for studies involving delicate or easily disrupted cell types (41). On the other hand, the MULTI-seq protocol has the greatest potential for achieving ultra-high multiplexing (20) and thus lower costs, although it required a larger number of input cells and was more time-consuming compared to the other methods.…”
Section: Discussionmentioning
confidence: 99%